Devlin, el pirata : en busca del oro de los franceses - Keating, Mark (Novelist) (Edhasa, 2013)
An injured French officer struggles along a desolate stretch of West African coastline, desperate to hold on to his secret. Alas for him, his tale is soon ended, and violently, but a young pirate recruit, Patrick Devlin, who happens to speak fluent French, comes away from their encounter with a new pair of boots and a treasure map. From there the adventures of the pirate Devlin, his shipmates, and those who wish them dead move forward without restraint, through broadside barrages and subterfuge and brutal encounters on land and at sea, where nothing is as it appears to be at first glance.